Legal Protection for Buyer Against Buying and Selling of Land Rights Performed Under Hand - Abidin Abidin; Teuku Syahrul Ansari; Bambang Daru (LEGAL BRIEF, 2022)
Legal institutions known in customary law are generally institutions that are needed to meet the needs of people who are still simple, so that in order to fulfill an open modern society, the institution of buying and selling land rights, for example, undergoes modernization and adjustment, without changing its nature as the legal act of buying and selling land rights with the payment of the price in cash, as well as the nature and characteristics of it as a real and clear act. A change that aims to improve the quality of evidence of legal acts carried out according to the customary law of the community which is limited in its personal and territorial scope, it is enough that the deed is made by the seller himself and known by the Village/Customary Head. The purpose of this study is to analyze, describe and provide legal protection for buyers against buying and selling land rights that are carried out under the hands. The research conducted in this paper is empirical research, using a sociological juridical approach. Based on the results of the research above regarding legal protection for buyers against those carried out on illegal sale and purchase of land rights, it can be concluded (1) the buyer does not get legal protection for the land he bought; (2) the buyer does not get legal certainty over the land he bought; (3) the buyer does not get strong evidence against the rights to the land he bought. This of course will be detrimental to the buyer who purchases land rights under his own hands. This incident is expected to raise awareness to the public, especially for buyers, when buying and selling land rights must be carried out before the PPAT so that they get protection and legal certainty for the land they buy.